Implementation of Extension Journalism in Cyber Media as a Communication Channel for Sustainable Development - Metha Madonna; Fikri Reza (Journal of Science and Science Education, 2023)
Use Ideally the national press supports the government through counselling-oriented journalism as a form of development communication. The concept of counselling journalism reflects the success of the "newspaper through the village" (Koran Masuk Desa) program in the 1980s as a form of press participation in development the impact was development are directed and economic stability. Replicating the development press concept in counselling journalism is crucial because currently the dissemination of information and mass media coverage in Indonesia is dominated by infotainment and fake news or viral issues that cannot be accounted for.  While on the other hand the Government must continue to developed the society. Objective: The research produces a conceptual design or model of counselling journalism that will be adopted and applied in the mass media. Methods: The research was conducted using a qualitative approach with a constructivist paradigm. The choice of case study method is based on a limited and significant unit of analysis, namely HarianPelita.id, which is a cyber media product of media convergence of one of the KMD. Results: The concept of counselling journalism can be categorized as news which is 1. educative and innovative, 2. inspiring and evocative, 3. literary, 4. influencing